2019
DOI: 10.1186/s41610-018-0097-9
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in winter activity of hibernating greater horseshoe bats (Rhinolophus ferrumequinum) from Korea

Abstract: Background: Hibernating bats exhibit ubiquitous winter activity in temperate zones, but there is considerable between-and within-species variety in their intensity and purpose. Bats may fly during winter for sustenance or travel to other hibernacula. This study compared inter-regional variation in the winter activity of the greater horseshoe bat (Rhinolophus ferrumequinum). We predicted that weather and hibernacula-environmental conditions would influence winter activity patterns. Results: Winter activity patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…In contrast, the mean daily RH was lower and the variance was greater in H1 than A1. Given that these microenvironment parameters were consistent with a previous study conducted in the same place [ 30 ], the higher creatinine concentrations in H1 might be related with higher TA and lower RH in H1 that could cause higher evaporative water loss [ 37 ]. However, we could not rule out the possibility that the higher creatinine concentrations in H1 were related to frequent or longer arousal that can result in increase of glomerular filtration rate and an increase in the accumulation of urinary creatinine in bladder [ 13 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In contrast, the mean daily RH was lower and the variance was greater in H1 than A1. Given that these microenvironment parameters were consistent with a previous study conducted in the same place [ 30 ], the higher creatinine concentrations in H1 might be related with higher TA and lower RH in H1 that could cause higher evaporative water loss [ 37 ]. However, we could not rule out the possibility that the higher creatinine concentrations in H1 were related to frequent or longer arousal that can result in increase of glomerular filtration rate and an increase in the accumulation of urinary creatinine in bladder [ 13 ].…”
Section: Discussionsupporting
confidence: 86%
“…However, we could not rule out the possibility that the higher creatinine concentrations in H1 were related to frequent or longer arousal that can result in increase of glomerular filtration rate and an increase in the accumulation of urinary creatinine in bladder [ 13 ]. In addition, as hibernating greater horseshoe bats can shift their roosting location within and between hibernacula [ 30 , 38 ], the urinary creatinine differences between A1 and H1 might not result solely from microenvironment differences. Further investigation on arousal frequency and metabolic rate between the two mineshafts will elucidate the reason for the creatinine differences between the two hibernacula.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar plugs are known to exist in other mammals, such as rodents, lipotyphlans, and marsupials (Austin and Short 1972;Rochel et al 2007;Martin et al 2011). It has been reported that R. ferrumequinum can interrupt hibernation (Sano 2001;Kim et al 2019). In the Japanese R. cornutus species, evidence of forced mating during hibernation periods has been recently reported, and the functional significance of the vaginal plug for deterring other males during hibernation period has been pointed out (Sato 2019).…”
Section: Discussionmentioning
confidence: 70%
“…The percentage of body mass lost (17-20%) by P. k. lepidus over three months of winter hibernation is similar to that of many underground hibernators such as Myotis daubentonii, Barbastella barbastellus and Rhinolophus ferrumequinum (e.g. Lesinski 1986;Kokurewicz 2004;Kim et al 2019).…”
Section: Structure and Sex Ratiomentioning
confidence: 63%